Global, regional and national burden of inflammatory bowel disease in 204 countries and territories from 1990 to 2019: a systematic analysis based on the Global Burden of Disease Study 2019 - Wang, Rui; Li, Zhaoqi; Liu, Shaojun; Zhang, Decai (BMJ open, 2023)
ObjectivesWe aimed to provide the most updated estimates on the global burden of inflammatory bowel disease (IBD) to improve management strategies.DesignWe extracted data from the Global Burden of Disease (GBD) 2019 database to evaluate IBD burden with different measures in 204 countries and territories from 1990 to 2019.SettingStudies from the GBD 2019 database generated by population-representative data sources identified through a literature review and research collaborations were included.ParticipantsPatients with an IBD diagnosis.OutcomesTotal numbers, age-standardised rates of prevalence, mortality and disability-adjusted life-years (DALYs), and their estimated annual percentage changes (EAPCs) were the main outcomes.ResultsIn 2019, there were approximately 4.9 million cases of IBD worldwide, with China and the USA having the highest number of cases (911 405 and 762 890 (66.9 and 245.3 cases per 100 000 people, respectively)). Between 1990 and 2019, the global age-standardised rates of prevalence, deaths and DALYs decreased (EAPCs=−0.66,–0.69 and −1.04, respectively). However, the age-standardised prevalence rate increased in 13 out of 21 GBD regions. A total of 147 out of 204 countries or territories experienced an increase in the age-standardised prevalence rate. From 1990 to 2019, IBD prevalent cases, deaths and DALYs were higher among females than among males. A higher Socio-demographic Index was associated with higher age-standardised prevalence rates.ConclusionsIBD will continue to be a major public health burden due to increasing numbers of prevalent cases, deaths and DALYs. The epidemiological trends and disease burden of IBD have changed dramatically at the regional and national levels, so understanding these changes would be beneficial for policy makers to tackle IBD.